Challenges and strategies in pediatric oncology palliative care in low-middle income countries: a systematic review - Sri Mulatsih; Clements Nicodhemus Garuda Nagara; Petra Gusti Parikesit; Ardhinta Bellano Septarda; Alvina Terencia; Devie Kristiani (Indonesian Pediatric Society, 2026)
Background Annually, over 400,000 children aged 0–19 are diagnosed with cancer, with low-middle income countries (LMICs) facing lower cure rates and higher mortality. Most Asian nations, especially in Southeast Asia, have limited palliative care services due to funding, workforce, regulatory, and medication access challenges. Objective To enhance pediatric oncology palliative care in LMICs by identifying barriers and effective strategies across diverse settings. Methods A systematic literature review was conducted in accordance with PRISMA guidelines, utilizing six major databases—PubMed, ScienceDirect, Cochrane Library, Lippincott Home, Sage Journals, and Google Scholar—to identify studies published from January 2015 until February 2025. We used the PICO framework and specific keywords to find studies. Results A total of 484 records were initially identified across multiple databases. From the final seven studies included, the main challenges of pediatric oncology palliative care in LMICs are limited access to healthcare facilities, resource scarcity, and difficulties surrounding end-of-life care. To address these issues, frequently adopted strategies include enhancing human resource capacity through training, establishing multidisciplinary teams, adapting policies and cultural approaches for integrated management, as well as developing affordable, and accessible interventions. Conclusion This systematic review identified the primary problems of pediatric oncology palliative care in LMICs, a shortage of adequately trained personnel, policy limitations, as well as cultural, financial, and social obstacles impeding effective care delivery. These findings highlight the need for comprehensive, culturally sensitive, and resource-conscious approaches to enhance the quality and accessibility of pediatric palliative care in similar settings.